Exclusão financeira e sua relação com a pobreza e desigualdade de renda no Brasil - Tonyedson Pereira e Lana (2013)
The main purpose of this research was to investigate possilbe relationships between financial exclusion, poverty and unequality of earned income in Brazil. In order to achieve it, a few hypothesis about this relationship were stated and, using the database of the Research on Family Budget from the Brazilian Institute of Geography and Statistics (IBGE), some empirical strategies were traced for verification. The first of them assumed that, despite its admittedly developed financial market, Brazil still had an elevated contingent on individuals laid aside of the system. Even aware that poorest families are the most affected by the problem of financial exclusion, as evidenciated on previous works, we considered the possibility that it was an additional element between the various issues that permeate the multidimensionality of poverty and unequality of earned income in Brazil. Also, as an essencial hypothesis, this research supported the thesis that the current politics of income transference in Brazil could be capable of increasing the level of integration of the beneficiaries with its financial system. And that, on a scenary like this, it would launch an important opportunity of complementing the efforts on promotion of inclusion, specially through the incorporation of strategies on financial alphabetization to the existing programs. In order to confirm and enrich those premises, the first part of this work was dedicated to demilitating the problem on financial exclusion, its causes, consequences and possible politics for coping with it. It did not aim, therefore, to provide theoretical contributions to the topic, but, opposingly, to find on the studies of its main authors, the motivations and adequate strategies to study the problem in Brazil. In sequence, the research proposed a series of empirical exercises that, in general lines, was founded in three steps. On the first one, we compiled, on several parts of this work, descriptive analysis that provided evidences on the contribution of economic, social, demographical and regional aspects on possession and consumption of financial products and services among the brazilian domiciles on the period of years 2002-03 and 2008-09. After confirming that many of those elements were relevant, the second empirical approach of this research relied on the methodology of data grouping in order to elaborate complex profiles for brazilian domiciles. The adoption of this multivaried approach has proven to be adequate to the stated hypothesis and allowed the proposition of preponderant family types in the country, and, specially, the identification of its financial behaviour during that period. The results were confirmed not only by the qualitative observation, but also by the quantification of the level and probability of financial inclusion, given by the builded index of exclusion, which was used on several econometric estimatives. The regressions, the building of the index that gathered the financial products and services made available by the POF, ended the set of empirical strategies of this work. By the end, the descriptive and econometric analysis showed important differences on financial behaviour between beneficiary and non-beneficiary domiciles eligible to the current income transference politics in Brazil. The results confirmed the stated hypotheis and suggested that inserting strategies against financial exclusion into anti-poverty politics may contribute significantly to increase citizenship, welfare and social inclusion of its target public.